Moral Education Perspective of Shaykh Nawawi Al-Bantani in the Book of Maraqi Al-'Ubudiyah and Shaykh Hafidz Hasan in the Book of Taisir Al-Khalaq - Jamastuti; Ainal Gani; Rumadani Sagala (Bulletin of Science Education, 2024)
In this digital era, moral degradation among teenagers is very worrying. Moral degradation that occurs includes promiscuity, free sex, increasing rates of violence among students, crimes against friends, theft, fraud, and drug abuse, pornography, assault, theft with violence, and destruction of other people's property. This condition has become a social problem which has not yet been fully resolved. So it is necessary to study in depth regarding morals. Based on the type, this research uses the type of library research, because the object of study is the result of written work which is the result of people's thoughts. This research uses library data collection techniques, namely reading and extracting the contents of related books. The data analysis technique in this research is using content analysis techniques. The results of the research concluded that the thoughts of Shaykh Nawawi Al-Bantani in the book Maraqi Al-Ubudiyah, the concept of moral education includes (1) Morals towards Allah SWT (2) Ethics towards educators (3) Ethics towards students, (4) Ethics towards children towards other people. old (5) Ethics towards people you don't know. (6) Ethics in socializing. Meanwhile, the concept of Moral Education in the Book of Taisirul Kholaq includes (1) Morals towards Allah SWT (2) Habits of Teachers and Students (3) Ethics towards oneself and others. (4) Daily Habits.